The Implementation of Javanese Local Wisdom Values as Strengthening the Practice of Pancasila - Bambang Sumardjoko; Arif Subowo (Universitas Sebelas Maret, 2021)
For the Indonesian people, Pancasila is the basis of the state and way of life, as well as the state ideology. In practice, it appears that the practice of Pancasila values is still weak and concerning. If this phenomenon is not handled seriously, it can become a threat to the existence of Pancasila in society, nation, and state. Indonesia is a country whose society is multicultural, consisting of various religions, races, tribes, cultures, and ethnicities, but has noble values that have been passed down from our ancestors to be preserved, namely Pancasila which unites the Indonesian nation. The Indonesian state consists of regions that have different local wisdom values. These values become guidelines and are cared for by all elements of society because they provide convenience in realizing national values. Even though each region has different local wisdom values, the Indonesian people remain united, namely ‘Bhineka Tunggal Ika’. There are many Javanese local wisdoms and for people who uphold the values of Javanese local wisdom, consciously or unconsciously, they have contributed significantly to the practice of Pancasila. The writing of this article is intended to describe the implementation of Javanese local wisdom values as a form of strengthening the practice of Pancasila. The main issues raised include the values of Javanese local wisdom, the practice of Pancasila values, and the implementation of Javanese local wisdom values as a form of strengthening the experience of Pancasila values. Materials and methods of writing articles use library research which is sourced from primary and secondary data, namely from expert informants, books, and relevant research journals. Finally, in this paper it is stated that the implementation of Javanese local wisdom values will be able to strengthen the practice of Pancasila values in the midst of a multicultural Indonesian society.